Extracts from The Cochrane Library: Erythropoietin as an adjuvant treatment with (chemo) radiation therapy for head and neck cancer. - Burton, M; Deschler, D; Rosenfeld, R (2009)
The "Cochrane Corner" is a quarterly section in the Journal that highlights systematic reviews relevant to otolaryngology-head and neck surgery, with invited commentary to aid clinical decision making. This installment features a Cochrane Review entitled "Erythropoietin as an adjuvant treatment with (chemo) radiation therapy for head and neck cancer," which concludes that erythropoietin should not be administered as an addition to radiation therapy outside the experimental setting.